Joint perception: gaze and social context - Richardson, Daniel C.; Street, Chris N.; Tan, Joanne Y.; Kirkham, Natasha Z.; Hoover, Merrit A.; Ghane Cavanaugh, Arezou (Frontiers in Human Neuroscience, 2012)
We found that the way people looked at images was influenced by their belief that others were looking too. If participants believed that an unseen other person was also looking at what they could see, it shifted the balance of their gaze between negative and positive images. The direction of this shift depended upon whether participants thought that later they would be compared against the other person or would be collaborating with them. Changes in the social context influenced both gaze and memory processes, and were not due just to participants’ belief that they are looking at the same images, but also to the belief that they are doing the same task. We believe that this new phenomenon of joint perception reveals the pervasive and subtle effect of social context upon cognitive and perceptual processes.